THE ROLE OF OSIS IN IMPROVING THE LEADERSHIP CHARACTER OF MA MIFTAHUL MIDAD LUMAJANG STUDENTS - Afandi, Ahmad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to determine how big the role of OSIS MA Miftahul Midad Lumajang is in improving student leadership character. This Intra-School Student Organization (OSIS) is a place to develop student talents and as a place to train themselves. Every school is obliged to form an OSIS besides having great benefits, it is also a legitimate organization and is recognized by the government.The research method chosen is a qualitative method with data collection techniques through observation, interviews and documentation. Sources of data were taken from interviews with key informants and documentation according to the object of research with informants including school principals, vice principals for student affairs, OSIS coaches, active OSIS administrators and students who are not OSIS administrators. Then analyzed by means of data reduction, data presentation and drawing conclusions. The results of research conducted at MA Miftahul Midad Lumajang regarding the role of OSIS in improving student leadership character can be concluded that OSIS is a space for students to express their ideas and talents, OSIS is a place for students to train themselves to be leaders by participating in many activities at school , the student council is a legitimate forum in schools so that students who are members of the student council are more visible in their leadership character due to their intensity in participating in activities.